How to treat new ideas - Horth, David Magellan; Mitchell, Michael T. (Center for Creative Leadership, 2017)
Annotation
Includes bibliographical references. - Online resource; title from title page (viewed January 3, 2018)
Keywords: Leadership -- Handbooks, manuals, etc; Technological innovations; Leadership; Guides, manuels, etc; Innovations; Leadership; handbooks; Handbooks and manuals; Guides et manuels; Handbook